ANALISIS RANTAI NILAI USAHA AGROINDUSTRI IKAN PATIN SALAI DI DESA PENYASAWAN KECAMATAN KAMPAR KABUPATEN KAMPAR - Adi Wahyu Dwi Nugroho Nugroho; Novia Dewi; Jumatri Yusri (Universitas Lancang Kuning, 2017)
This study aims to identify the value chain of catfish agroindustry in Desa Penyesawan, to analyze the value or margin received on each chain involved in salted catfish agro industry and to analyze the added value of catfish salai in Desa Penyesawan. The method of determining the sample using purposive sampling method. With this method got 9 business agent of catin fish salt agroindustry as research sample. Data analysis method used is descriptive method of quantitative and qualitative. The data used in this study is the primary data in the form of questionnaires in the form of questionnaires and secondary data in the form of data obtained from relevant agencies. Result of research indicate that there are 2 pattern of value chain that is pattern I: farmer-perpetrator of business-consumer (19,26) and pattern II: farmer-perpetrator of business-merchant retailer-consumer (10,41). The comparison of marketing efficiency at the same actor level shows that the value chain of pattern II is more efficient than the value chain of pattern I (10.41).